2012
DOI: 10.1155/2012/284301
|View full text |Cite
|
Sign up to set email alerts
|

Clerodendrum inermeLeaf Extract Alleviates Animal Behaviors, Hyperlocomotion, and Prepulse Inhibition Disruptions, Mimicking Tourette Syndrome and Schizophrenia

Abstract: Previously, we found a patient with intractable motor tic disorder, a spectrum of Tourette syndrome (TS), responsive to the ground leaf juice of Clerodendrum inerme (CI). Here, we examined the effect of the ethanol extract of CI leaves (CI extract) on animal behaviors mimicking TS, hyperlocomotion, and sensorimotor gating deficit. The latter is also observed in schizophrenic patients and can be reflected by a disruption of prepulse inhibition of acoustic startle response (PPI) in animal models induced by metha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Although MIH is not an animal model specifically resembling TS/tic disorders, it represents a hyper-dopaminergic status in animals that may mimic several other neurospsychiatric disorders with hyperdopaminergic activity, such as schizophrenia and OCD. Previously, we have demonstrated that haloperidol, a dopamine D2 receptor blocker effective for treating TS/tic clinically although causing extrapyramidal side effects, was effective in the same MIH model (Chen et al, 2012). Hispidulin was effective by i.p.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Although MIH is not an animal model specifically resembling TS/tic disorders, it represents a hyper-dopaminergic status in animals that may mimic several other neurospsychiatric disorders with hyperdopaminergic activity, such as schizophrenia and OCD. Previously, we have demonstrated that haloperidol, a dopamine D2 receptor blocker effective for treating TS/tic clinically although causing extrapyramidal side effects, was effective in the same MIH model (Chen et al, 2012). Hispidulin was effective by i.p.…”
Section: Discussionmentioning
confidence: 85%
“…CI leaves were collected from mangrove marshes in the riverside of southern Taiwan and stored as reported in our previous study (Chen et al, 2012). A CI leave sample from the same batch was deposited as a voucher specimen (TMU27423) in the herbarium of College of Pharmacy, Taipei Medical University.…”
Section: Plant Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Classical and atypical antipsychotics that are clinically used have been shown to selectively inhibit CAR [16]. FP as well as clozapine effectively [41], Catha edulis [42], Glycyrrhiza glabra [43] or Clerodendrum inerme [44] are known to induce PPI deficits in rodents.…”
Section: Discussionmentioning
confidence: 99%